Mutakalimin's View on the Vision of Allah (Ru’yatullah) - Harda Armayanto; Adib Fattah Suntoro; Martin Putra Perdana (Santri: Journal of Pesantren and Fiqh Sosial, 2022)
The problem of ru'yatullah (vision of Allah) is one of the problems of kalam that is still the topics of intense debate nowadays . This problem is specifically discussed by three schools of kalam: mu'tazilah, shi'ah, and ahl al-sunnah wa al-jama'ah. Each group claims that their understanding is the most truthful. This research aims to show how the strengths and weaknesses of each group are based on their epistemological doctrines and argumentation. This study is categorized as a literature review utilizing the documentation of data collection methodology. The collected data will be analyzed utilizing content analysis technique as well as the kalam scientific approach. The results of this research expose that the ahl al-sunnah wa al-jama'ah's opinions are more valid from an epistemological standpoint because they are based on a harmonization between the rationality of reason and the textuality of revelation.